In vivo effects of javamide-I/-II on metabolic, hepatic, cardiovascular and inflammatory risk factors - Park, Jae B.; Peters, Renee (Frontiers in Nutrition, 2025)
BackgroundJavamide-I/-II (J1/J2) are bioactive compounds found in coffee. Recent studies suggest that J1/J2 may possess anti-inflammatory activity. However, there is no information about the effects of J1/J2 on inflammatory cytokines and other health-related factors in vivo.MethodsTo investigate the effects of J1/J2 on inflammatory and other health-related factors (metabolic/growth/hepatic/cardiovascular/ risk factors) in vivo, rats were placed into two groups: CG group (a control diet/drinking water, n = 10) and JG group (a normal diet/drinking water containing J1/J2, n = 10). The study was performed for 16 weeks. During the study, bodyweight and water consumption were monitored weekly, and O-red/HE stains, ALT, AST, IGF1, IGF-1, growth hormone, sE-selectin, sICAM, TNF-alpha, and MCP-1 assays were performed using histochemistry and ELISA methods. The amounts of J1/J2 were measured by HPLC.ResultsThe average daily intakes of J1 and J2 were found to be about 0.13 and 0.38 mg, respectively, and no significant difference in bodyweight was found between the CG and JG groups. Also, O-red/HE stains showed no significant difference between both groups, suggesting that J1/J2 may have no adverse effect on the liver. Also, there was no difference in ALT level between both groups. However, the level of AST was significantly lower in the JG group compared to the CG group (p < 0.05). Additionally, J1/J2 had no significant effects on growth hormone (GH) and IGF-1 in the JG group, compared to the CG group. Also, there was no significant difference in sE-selectin and sICAM levels between both groups. However, TNF-alpha and MCP-1 levels were significantly lower in the JG group, compared to the CG group (p < 0.05), suggesting that J1/J2 may have positive effects on these inflammatory cytokines in vivo.ConclusionJ1/J2 may have beneficial effects on hepatic and inflammatory factors (AST, TNF-alpha and MCP-1) without adverse effects on bodyweight, liver, ALT, GH, IGF-1, sE-selectin, and sICAM in rats.